A review of the genus Parorthocladius Thienemann, 1935 (Diptera: Chironomidae: Orthocladiinae) from the Russian Far East - Makarchenko, Eugenyi A.; Makarchenko, Marina A. (Zootaxa, 2015)
Three new species of the genus Parorthocladius Thienemann, P. lazovskiensis sp. nov., P. plolabius sp. nov., and P. tyurkini sp. nov. from the Russian Far East are described and figured. Descriptions of pupae and larvae of one indeterminate species, Parorthocladius sp. 1, are also presented. Keys to determination of adult males, pupae and fourth instar larvae of Far-Eastern species Parorthocladius are provided.